Conservación y viabilidad de varetas en la multiplicación clonal de cacao (Theobroma cacao L.) CCN-51 - Veliz Arana, Douglas Joel (2017)
In Ecuador, cocoa represents the third item of agricultural exports and constitutes a source of direct and indirect employment to the country. However, most of the national cocoa plantations are old and unproductive, representing a problem for farmers directly dependent on this crop. The use of the rod grafting method should be complemented with methodologies for the conservation of plant material for later use without losing its vigor, which is why we establish the present research that seeks to determine the effect of temperature variations on conservation and subsequent viability of the plant material, for which a complete randomized experimental design with a factorial arrangement 4x3 was established, being for factor A the conservation temperature levels (ambient, 12, 6 and 3° C), while for Factor B established conservation periods (24, 48 and 72 hours). The variables evaluated were: stunting (PP), number of shoots (NB), shoot height (AB), shoot diameter (DB) and leaf number (NH). The results obtained allowed to establish that PP was affected by the interaction between the factors A * B, reaching 95% at room temperature and 24 hours of preservation; the vigor of the rods was not affected when reaching 12 ° C, regardless of the shelf life, reaching values of NB, AB, DB and NH similar at room temperature and even higher. The conservation periods did not have a significant effect on the evaluated variables.